ANTIOXIDANT, ANTIBACTERIAL AND HEPATOPROTECTIVE ACTIVITIES OF CISSUS REPENDA VAHL ON CARBON TETRACHLORIDE (CCL4) INDUCED LIVER DAMAGE IN BIRD COLUMBA LIVIA - Kardong, D.; Purkayastha, B.; Upadhyaya, S.; Chetia, J. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: Drug induced liver damage has been identified as one of the major global diseases in recent years. The plant derived alternative medicines are considered as the most effective solution for combating such liver diseases. In the present study, the antioxidant, antibacterial and hepatoprotective property of Cissus rependa Vahl. was evaluated. Methods: Anti-oxidant activity of the extracts were spectrophotometrically determined using ascorbic acid as standard. Determination of antimicrobial activity followed by Agar well diffusion method and nutrient content by standard laboratory methods. The activity of the two enzymes were measured spectrophotometrically (520 nm) following the DNPH method with minor modification Â  Results: The study shows that the aqueous extract of the plant leaf contains a good number of phytochemicals such as cardiac glycoside, saponin, alkaloid etc. as well as antioxidant with respect to the scavenging activity against free radicals DPPH (79.79 %) and ABTS (84.6%) which were roughly comparable to that of ascorbic acid (88.2% and 83.0 % respectively). The plant extract also exhibited potent antibacterial activity against S. aureus and P. vulgaris indicating its bactericidal or bacteriostatic properties. The study also indicates that the oral feeding of aqueous extract of the plant could reduce the CCl4 induced chronic damage of hepatic tissue in bird (C. livia) which was reflected by the decreased level of total soluble protein as well as activity of the enzymes Aspertate aminotransferase (AST) and Alanin aminotransferase (ALT) in both liver and muscle tissues of EX (experimental) group treated with plant extract as compared to that of untreated birds PC (positive control) group which otherwise had highly increased due to CCl4 induced tissue damages. Key words: Antioxidants, Cissus rependa Vahl, hepatotoxicity, Aspertate aminotransferas and phytochemicals.